SARS-CoV-2 Antibodies Mediate Complement and Cellular Driven Inflammation - Jarlhelt, Ida; Nielsen, Sif Kaas; Jahn, Camilla Xenia Holtermann; Hansen, Cecilie Bo; Pérez-Alós, Laura; Rosbjerg, Anne; Bayarri-Olmos, Rafael; Skjoedt, Mikkel-Ole; Garred, Peter (Frontiers in Immunology, 2021)
The ongoing pandemic of coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to constitute a serious public health threat worldwide. Protective antibody-mediated viral neutralization in response to SARS-CoV-2 infection has been firmly characterized. Where the effects of the antibody response are generally considered to be beneficial, an important biological question regarding potential negative outcomes of a SARS-CoV-2 antibody response has yet to be answered. We determined the distribution of IgG subclasses and complement activation levels in plasma from convalescent individuals using in-house developed ELISAs. The IgG response towards SARS-CoV-2 receptor-binding domain (RBD) after natural infection appeared to be mainly driven by IgG1 and IgG3 subclasses, which are the main ligands for C1q mediated classical complement pathway activation. The deposition of the complement components C4b, C3bc, and TCC as a consequence of SARS-CoV-2 specific antibodies were depending primarily on the SARS-CoV-2 RBD and significantly correlated with both IgG levels and disease severity, indicating that individuals with high levels of IgG and/or severe disease, might have a more prominent complement activation during viral infection. Finally, freshly isolated monocytes and a monocyte cell line (THP-1) were used to address the cellular mediated inflammatory response as a consequence of Fc-gamma receptor engagement by SARS-CoV-2 specific antibodies. Monocytic Fc gamma receptor charging resulted in a significant rise in the secretion of the pro-inflammatory cytokine TNF-α. Our results indicate that SARS-CoV-2 antibodies might drive significant inflammatory responses through the classical complement pathway and via cellular immune-complex activation that could have negative consequences during COVID-19 disease. We found that increased classical complement activation was highly associated to COVID-19 disease severity. The combination of antibody-mediated complement activation and subsequent cellular priming could constitute a significant risk of exacerbating COVID-19 severity.